Smart Door Locks Based on Internet of Things Concept with mobile Backend as a Service - Mahali, Muhammad Izzuddin (Elinvo (Electronics, Informatics, and Vocational Education), 2016)
Smart Door Locks System Based on Internet of Things Concept with Mobile Backend as s Service is the smart door locks development are supported by cloud computing technology as data storage. Methods of development that exist in this system is to combine technology (1) ESP8266 (2) Firebase and (3) Android Apps. Firebase is one of cloud-based services that are used to store data online. ESP8266 able to communicate with firebase well to process the read and write data directly using internet communication channels. Android application used to direct communication to the firebase for monitoring and  controlling simultaneously to the system. Android app can control / monitoring Indirectly to ESP8266 module via Firebase that serves as a mobile Backend as a Service to apply the rules of the Internet of Things